2013
DOI: 10.1021/am401131u
|View full text |Cite
|
Sign up to set email alerts
|

Surprising High Hydrophobicity of Polymer Networks from Hydrophilic Components

Abstract: We report a simple and inexpensive method of fabricating highly hydrophobic novel materials based on interpenetrating networks of polyamide and poly(ethyl cyanoacrylate) hydrophilic components. The process is a single-step solution casting from a common solvent, formic acid, of polyamide and ethyl cyanoacrylate monomers. After casting and subsequent solvent evaporation, the in situ polymerization of ethyl cyanoacrylate monomer forms polyamide-poly(ethyl cyanoacrylate) interpenetrating network films. The interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
4
8
0
Order By: Relevance
“…3. The degradation of nylon 6,6 takes place between 350 C and 500 C, as reported by earlier studies, and only about 2% remains at 600 C. 25,26 The weight loss of composites is gradual and the remaining material at 600 C increases with the GnP loading. It is seen that all lms do not decompose at the same temperature, but as GnP concentration increases (except for 0.1 wt% GnP), the decomposing temperature slightly shis to higher values.…”
Section: Thermal Properties (Tga)supporting
confidence: 63%
“…3. The degradation of nylon 6,6 takes place between 350 C and 500 C, as reported by earlier studies, and only about 2% remains at 600 C. 25,26 The weight loss of composites is gradual and the remaining material at 600 C increases with the GnP loading. It is seen that all lms do not decompose at the same temperature, but as GnP concentration increases (except for 0.1 wt% GnP), the decomposing temperature slightly shis to higher values.…”
Section: Thermal Properties (Tga)supporting
confidence: 63%
“…This indirectly suggests that the polymers interact with strong hydrogen bonds, leaving no interacting polar groups on the surface of the films. Similar systems were also reported earlier, in which two hydrophilic polymers were hybridized, thereby forming hydrophobic composite films [ 42 ]. The dynamic water contact angle measurements reported in Figure 6 b show that the contact angles change slightly over a period of 2 min under ambient conditions which can be attributed to the evaporation of the droplets rather than droplet absorption into the film or a sudden change in wetting state [ 42 ].…”
Section: Resultssupporting
confidence: 75%
“…Similar systems were also reported earlier, in which two hydrophilic polymers were hybridized, thereby forming hydrophobic composite films [ 42 ]. The dynamic water contact angle measurements reported in Figure 6 b show that the contact angles change slightly over a period of 2 min under ambient conditions which can be attributed to the evaporation of the droplets rather than droplet absorption into the film or a sudden change in wetting state [ 42 ]. Separately, the water absorption tests for all the films that extend to a two-week period are reported in Figure 6 c. The pure PU film was very stable and its water uptake remained below 5% compared to pure PVP that completely dissolves in water after a couple of hours.…”
Section: Resultssupporting
confidence: 75%
“…Direct modification of PK with diamines resulted in a dramatic increase of the tensile strength of PK [ 27 ]. It was also found that hydrogen bonding between PK and PECA resulted in interpenetrating networks by which wettability and morphology can be controlled [ 28 ].…”
Section: Introductionmentioning
confidence: 99%